Product Innovation and Marketing Strategy of Culinary MSMEs in Improving Local Competitiveness - Dian Milasari; Siti Yunitarini; Kamalina Din Jannah; Komala Ardiyani; Naufalia Sabrina Putri (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the form of product innovation and marketing strategies implemented by culinary MSMEs in Pekalongan in order to improve the competitiveness of their businesses in the local market. The approach used is descriptive qualitative with explorative case study method. Data were collected through in-depth interviews, participatory observations, and documentation from MSME actors who have been active for at least two years. The results showed that product innovation was carried out through menu diversification, the useof location materials, and creative packaging, while marketing strategies evolved towards digital, utilizing social media, food delivery services, and collaborative promotions. The integration between product innovation and marketing strategy has proven to increase turnover, expand the market, and strengthen the brand identity of MSMEs. This study recommends the need for training, mentoring, and supporting policies from local governments as well as collaboration with academics to strengthen the MSME ecosystem based on local potential.